Nucleoside-modified mRNA vaccines induce potent T follicular helper and germinal center B cell responses - Pardi, Norbert; Hogan, Michael J; Naradikian, Martin S; Parkhouse, Kaela; Cain, Derek W; Jones, Letitia; Moody, M Anthony; Verkerke, Hans P; Myles, Arpita; Willis, Elinor; LaBranche, Celia C; Montefiori, David C; et al. (The Journal of experimental medicine, 2018)
T follicular helper (Tfh) cells are required to develop germinal center (GC) responses and drive immunoglobulin class switch, affinity maturation, and long-term B cell memory. In this study, we characterize a recently developed vaccine platform, nucleoside-modified, purified mRNA encapsulated in lipid nanoparticles (mRNA-LNPs), that induces high levels of Tfh and GC B cells. Intradermal vaccination with nucleoside-modified mRNA-LNPs encoding various viral surface antigens elicited polyfunctional, antigen-specific, CD4 T cell responses and potent neutralizing antibody responses in mice and nonhuman primates. Importantly, the strong antigen-specific Tfh cell response and high numbers of GC B cells and plasma cells were associated with long-lived and high-affinity neutralizing antibodies and durable protection. Comparative studies demonstrated that nucleoside-modified mRNA-LNP vaccines outperformed adjuvanted protein and inactivated virus vaccines and pathogen infection. The incorporation of noninflammatory, modified nucleosides in the mRNA is required for the production of large amounts of antigen and for robust immune responses.